Pengembangan LKPD Fisika Berbasis Android dengan Pendekatan Saintifik pada Materi Usaha dan Energi - Syalomita Sihite; Irham Ramadhani (Mataram University, 2026)
Physics learning on Work and Energy still faces challenges in the form of students' poor understanding of abstract concepts and the suboptimal use of digital technology as a learning medium. Therefore, the development of Android-based worksheets with a scientific approach is necessary to support more interactive and meaningful learning. This study aims to develop an Android-based physics student worksheet (LKPD) with a scientific approach to the topic of Work and Energy and to test its validity, practicality, and effectiveness. This study employed the Research and Development (R&D) method with the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The subjects were 11th-grade students of SMA Negeri 1 Lae Parira, selected using cluster random sampling. The research instruments included validation sheets from material experts and media experts, questionnaires from educators and students, and learning outcome tests. Data were analyzed descriptively using quantitative percentages and the N-Gain test. The results showed that the developed Android-based physics LKPD achieved a very high level of validity, with validation percentages from media experts of 94.5% and from material experts of 93.5%. The practicality level based on educator responses reached 93%, while student responses in the small-group and large-group tests were 90.51% and 89.25%, respectively, categorized as very practical. The effectiveness test results showed an increase in student learning outcomes with an average pretest score of 58.82 and a posttest score of 88.16, along with an N-Gain score of 0.70, which is categorized as moderate. Thus, the Android-based physics worksheet with a scientific approach to the Work and Energy material is declared valid, practical, and effective for use in physics learning.